Energetically significant unconventional OH⋯π contacts involving discrete guest (H2O)8 clusters in a fumarato bridged polymeric supramolecular host of Ni(II) phenanthroline: Antiproliferative evaluation and theoretical studies. (15th January 2020) - Nath, Hiren; Sharma, Pranay; Frontera, Antonio; Verma, Akalesh K.; Das, Amal; Barceló-Oliver, Miquel; Bhattacharyya, Manjit K.
Graphical abstract: Energetically significant unconventional OH⋯π interactions in a Ni(II) coordination polymer that has been analyzed by DFT calculations, MEP surface and NCI plot index. Anticancer activities considering cell cytotoxicity, apoptosis, molecular docking and pharmacophore features have been investigated to establish structure activity relationship of the polymer. Abstract: A new coordination polymer of nickel(II) involving bridging fumarato viz. catena [μ-fumarato(1, 10-phenanthroline monohydrate(diaqua))nickel(II)trihydrate], {[Ni(μ-fum)(phen)(H2 O)2 ] . 3H2 O}n (1 ) (where, fum = fumarate, phen = 1, 10-phenanthroline monohydrate) has been synthesized in purely aqueous medium at room temperature. The crystal structure of the polymer has been determined by single crystal X-ray Diffraction analysis. The polymer has been characterised by FT-IR, electronic spectroscopy, thermal and elemental analysis. The zig-zag polymeric chain of 1 self assembles into 2D supramolecular network architecture via reciprocal π-π stacking interactions. The lattice water molecules are involved in the formation of unique supramolecular octameric linear water clusters involving alternate trimeric rings that stabilizes the 2D network architecture. The crystal structure of the polymer also reveals the self-assembled enclathration of (H2 O)8 cluster into polymeric Ni(II) host involving fum ligands that brings rigidity to the structure. Theoretical calculations have been performed to analyse the non-covalent interactions observed in the solid-state structure of 1 . In particular, we have analysed the π–π stacking interactions between the phen ligands and also the energetically significant unconventional OH⋯π interaction involving the π-system of fum . For the latter, we have investigated the ability of the double bond of fum (coordinated to Ni) to establish OH⋯π interaction with water in comparison to fum acid and simple ethene. Finally, the polymer has been investigated for potential anticancer activities considering cell cytotoxicity, apoptosis and molecular docking as a major parameters against Dalton's lymphoma (DL) malignant cancer cell line and the results were compared with cisplatin (reference drug) under the same experimental conditions. DNA interaction and fragmentations have been investigated for compound 1 and pharmacophore features establish structure activity relationship (SAR).